A Road to Fīrūzābād - Rossi, Domiziana (Ex Novo: Journal of Archaeology, 2018)
A serpentine path created by the river Tang-āb through the Zagros Mountains has always been the only access from north to the city of Ardašīr-Xwarrah, located at five kilometers west from the modern Fīrūzābād, in Iran. This inaccessibility prompted the king of Fārs Ardašīr to found his stronghold against the Arsacid power here. This path endured the fall of the Sasanian Empire throughout Islamic times as a crossroads of the routes connecting the port of Sīrāf to other cities. The impervious path allowed both the coup d’État that marked the rise of the Sasanian dynasty and the development of trades through Fīrūzābād. The reliefs of Ardašīr’s victory over the Arsacid King and his investiture by the god Ohrmazd are carved in the gorge, ad perpetuam rei memoriam. Furthermore the rose-water produced in Fīrūzābād travelled on the steep path farsakh by farsakh (literally, parasang by parasang) so it could spread through the entire dār al-Islam. The movement of goods and populations on this road has survived with the Qashqaii nomads, who travel along this path even today, during their seasonal migration.